2021
DOI: 10.1123/jtpe.2019-0085
|View full text |Cite
|
Sign up to set email alerts
|

Middle School Students’ Perceptions of Physical Education: A Qualitative Look

Abstract: Purpose: Existing research suggests that students’ attitudes toward physical education are positive through Grade 5, but become less positive as grade levels increase; this research is, however, missing student voice. The purpose of this study was to further understand why students’ attitudes have been shown to decrease. Methods: Twenty-six focus group interviews (students N = 65) were conducted over 2 years to discover what was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 33 publications
0
15
0
3
Order By: Relevance
“…However, while access to facilities and budgets for equipment impact upon curricula decisions [80], sports and activities such as parkour, orienteering, skateboarding, and ultimate frisbee perhaps offer more 'cost effective' and achievable lifestyle sport options for PE teachers [8,22,81]. It is likely that a varied PE curriculum, incorporating lifestyle sports in some capacity, will reduce student boredom, repetitiveness, and offer an alternative beyond an overemphasis on competitive team sports [82].…”
Section: Discussionmentioning
confidence: 99%
“…However, while access to facilities and budgets for equipment impact upon curricula decisions [80], sports and activities such as parkour, orienteering, skateboarding, and ultimate frisbee perhaps offer more 'cost effective' and achievable lifestyle sport options for PE teachers [8,22,81]. It is likely that a varied PE curriculum, incorporating lifestyle sports in some capacity, will reduce student boredom, repetitiveness, and offer an alternative beyond an overemphasis on competitive team sports [82].…”
Section: Discussionmentioning
confidence: 99%
“…El 95,3% del estudiantado considera que el profesor los trata con respeto, lo que deja en evidencia que es un rasgo de la personalidad del docente muy valorado por sus estudiantes. El resultado, en este caso, es similar a los que han aportado otros estudios (Cárcamo, 2012, Gaviria & Castejón, 2016, Phillips et al, 2020.…”
Section: El Profesorunclassified
“…El interés por saber cómo perciben los estudiantes las clases de Educación Física, ha sido objeto de estudio por diversos autores en múltiples contextos (Arantes et al, 2018;Beltrán & Devís, 2019;Cárcamo et al, 2017, Daniel & Sousa, 2010, Dochy et al, 2002, Gaviria & Castejón, 2016, Kawashima, 2012, Murcia, 2007, Phillips, et al, 2020. Algunos temas abordados están referidos al profesor, el gusto por la clase, la motivación, el proceso didáctico (metodología, evaluación, recursos, contenidos), entre otros.…”
Section: Introductionunclassified
“…Therefore, this study aimed to empirically investigate Singapore students' perceptions of fitness testing across three school stages (primary, secondary, and pre-university) and between gender groups using valid and reliable instruments based on psychological theories (SDT; Deci and Ryan 1985;TPB;Ajzen 1991). Although researchers indicated that multiple students dislike the fitness test mile run (Ladwig, Vazou, and Ekkekakis 2018;Phillips et al 2020), it is still unknown which fitness test item is the most unpopular among students in the literature. A cluster analysis was also performed with students' identified motivational profiles to obtain an overview of their fitness testing perceptions.…”
Section: The Present Studymentioning
confidence: 99%
“…Adolescent females also tend to have more negative fitness testing perceptions than adolescent males (Luke and Sinclair 1991). Numerous students in some studies also demonstrated an aversion to fitness test mile run as running is not enjoyable (Ladwig, Vazou, and Ekkekakis 2018) and questioned its purpose (Phillips et al 2020). These less than ideal testing procedures and activities perpetuate students to become appalled, disinterested, and less intrinsically motivated (Zhu et al 2018).…”
Section: Introductionmentioning
confidence: 99%